2022 IEEE Canadian Conference on Electrical and Computer Engineering (CCECE) 2022
DOI: 10.1109/ccece49351.2022.9918481
|View full text |Cite
|
Sign up to set email alerts
|

Agglomerative Hierarchical Clustering with Dynamic Time Warping for Household Load Curve Clustering

Abstract: Energy companies often implement various demand response (DR) programs to better match electricity demand and supply by offering the consumers incentives to reduce their demand during critical periods. Classifying clients according to their consumption patterns enables targeting specific groups of consumers for DR. Traditional clustering algorithms use standard distance measurement to find the distance between two points. The results produced by clustering algorithms such as Kmeans, K-medoids, and Gaussian Mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Based on the minimal Davies-Bouldin Index (DBI), the authors found that the average linkage method performed relatively better than the others. Study in [29], applied Agglomerative Hierarchical Clustering with Dynamic Time Warping to classify residential households' daily load curves based on their consumption patterns. The proposed approach used Dynamic Time Warping (DTW) to find the best match between two load curves, whereas Agglomerative Hierarchical Clustering (AHC) was used to get a better starting point for the cluster centers.…”
Section: Clusteringmentioning
confidence: 99%
“…Based on the minimal Davies-Bouldin Index (DBI), the authors found that the average linkage method performed relatively better than the others. Study in [29], applied Agglomerative Hierarchical Clustering with Dynamic Time Warping to classify residential households' daily load curves based on their consumption patterns. The proposed approach used Dynamic Time Warping (DTW) to find the best match between two load curves, whereas Agglomerative Hierarchical Clustering (AHC) was used to get a better starting point for the cluster centers.…”
Section: Clusteringmentioning
confidence: 99%
“…Agglomerative Hierarchical Clustering employs a ''bottomup'' methodology, initially treating each data point as an individual cluster and successively merging pairs as we ascend the hierarchy. In power system applications, such as smart grid analytics, this approach can facilitate grouping power consumers with similar energy usage patterns [327], [328], [329], thereby enabling better demand forecasting and load balancing strategies [26].…”
Section: ) Agglomerative Hierarchical Clusteringmentioning
confidence: 99%